A democratização do poder nas empresas e a participação nos lucros ou resultados - PLR - Montanari, Ney Duarte (2008)
This academic study has its foundations fixed in the reflection of more than three and a half centuries of slavery, the compulsory work system, the monopoly of managerial power in the hands of de holders of the production means, the reflexes in the business and in the relationships among employee and employer in the current days, seen by the eyes of the law s analyses with focus in the company s economical life, its organization and the instruments of people s produced by the schools of administration and economy until the current days. It studies the Brazilian Constitutions, starting form de Imperial of 1.824 until the text of the current Great Letter, beside the legal system, the syndical structure, the mechanisms of conflicts solution, the information rights and de instruments of representation and worker s participation in the administration, in the profits and in the companies results. It presents the foundations and de evolution of the Administration Schools, starting from the scientific theory and personal relationship, through models identified as taylorism, fordism and toytism, reaching the organization and people s management, know as Administration by Objectives and Participant Administration. It exposes and analyses the instruments of de existing worker representation, passing through the internal committee of accidents, factory committee and worker representation, internal regulations, by the co-administration to focus in the larger objective of the dissertation and to demonstrate the reach and dimensions of the workers in the profits participation or results of de companies, instrument that in crumbled and discussed in full detail, highlighting its nature, purpose, economical advantages, flexibility, juridical safety and its model inspirations of democracy and humanization in the relationship between employee and employer